Distortion equation of motion in linear incompatible elastodynamics - Wojnar, R. (Archives of Mechanics, 1999)
The paper deals with an initial-boundary value problem of linear incompatible elastodynamics, based on Kosevich’ theory of continuonsly distributed defects due to prescribed plastic fields, [1, 2, 3]. In analogy to a stress formulation of linear incompatible elastodynamics with continuously distributed defects, [4], a distortion formulation is proposed. In such a formulation the tensorial inlitial-boundary value problem for an unknown asymmetric tensor field is to be solved. A solution to the problem generates the associated stress and rotation fields.